Use of off-label doses is frequent in biologic therapy for moderate to severe psoriasis: A cross-sectional study in clinical practice. (2nd November 2015) - Carrascosa, Jose-Manuel; Garcia-Doval, Ignacio; Pérez-Zafrilla, Beatriz; Carretero, Gregorio; Vanaclocha, Francisco; Daudén, Esteban; De la Cueva-Dobao, Pablo; Belinchón, Isabel; Alsina, Merce; López-Estebaranz, Jose-Luis; Ferrán, Marta; Torrado, Rosa; et al.
Abstract: Introduction : Biologic medications increase dramatically the burden of a chronic and high prevalent disease like psoriasis. The objective of the study was to quantify the use of dose reduction or dose escalation strategies, not reflected in the drug summary of product characteristics, in clinical practice. Methods : An observational, cross-sectional study of a subset of patients from the Spanish Registry for Systemic Treatments in Psoriasis (BIOBADADERM) treated for over six consecutive months with the same biologic agent. Results : The study included 637 patients. At the cut-off date, the initial dose had been reduced in 223 patients (35%; 95% CI: 31.3–38.9%) and escalated in 46 (7.2%; 95% CI: 5.3–9.5%). When compared with the patients treated with standard doses, the patients on reduced doses had a lower PASI score at the cut-off date (a mean 2.6 versus 1; −1.6 points) and exhibited greater improvement in PASI since the start of biologic therapy (mean reduction over baseline 75% versus 87%). By contrast, the patients receiving an escalated dose had higher PASI scores (2.6 versus 8.0) and showed less improvement in PASI (75% versus 46.8%). Conclusion : Off-label doses of biologic agents for psoriasis are frequent in clinical practice. This information is especially relevant for pharmacoeconomic models.